Spatial distribution of endogenous tissue protease activity in gastric carcinoma mapped by MALDI Mass Spectrometry Imaging - Erich, Katrin; Müller, Torsten; Abu Sammour, Denis; Hinsenkamp, Isabel; Gutting, Tobias; Burgermeister, Elke; Findeisen, Peter; Ebert, Matthias; Krijgsveld, Jeroen; Hopf, Carsten (Molecular & cellular proteomics, 2019)
Aberrant protease activity has been implicated in the etiology of various prevalent diseases including neurodegeneration and cancer, in particular metastasis. Matrixassisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) has recently been established as a key technology for bioanalysis of multiple biomolecular classes such as proteins, lipids, and glycans. However, it has not yet been systematically explored for investigation of a tissue’s endogenous protease activity. In this study, we demonstrate that different tissues, spray-coated with substance P as a tracer, digest this peptide with different time-course profiles. Furthermore, we reveal that distinct cleavage products originating from substance P are generated transiently and that proteolysis can be attenuated by protease inhibitors in a concentration-dependent manner. To show the translational potential of the method, we analyzed protease activity of gastric carcinoma in mice. Our MSI and quantitative proteomics results reveal differential distribution of protease activity - with strongest activity being observed in mouse tumor tissue, suggesting the general applicability of the workflow in animal pharmacology and clinical studies.
Gesehen am 02.07.2019